PAIKEM Implementation in Teaching the Concept of Salvation for Children Age 9-12: Implementasi PAIKEM dalam Pengajaran Konsep Keselamatan pada Anak Usia 9-12 Tahun - Kezia Tri Agustina; Debora Nugrahenny Christimoty; Karnawati (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2022)
People without exception have a need to be saved from the death. Likewise with children aged 9-12 years. These children are the age group with the highest number of people attending Sunday School. Physical characteristics of children aged 9-12 years are children who still like to move, play, and have a spirit that seems to never go out. Therefore we need a learning model that can really attract the attention of students. The PAIKEM model (Active, Innovative, Effective and Fun Learning) can be applied in teaching the concept of salvation which aims to change a person's life to become a disciple of Jesus. This research uses descriptive qualitative method. This study aims so that educators can understand the nature of students, get to know students personally and especially take advantage of student behavior in organizing learning. Furthermore, providing good feedback to improve learning activities so that they can experience a Christ-centered life. They can receive a real religious experience.